Literary Phenomenology in Ngaju Dayak Folklore - Poerwadi, Petrus; Misnawati, Misnawati; Manya, Manya; Maya Sari, Fina (Journal of World Science, 2023)
The objectives of this study are describing the phenomenology of plants in Ngaju Dayak folklore and describing the phenomenology of animals in Ngaju Dayak folklore. This research method uses a qualitative approach. Qualitative research is a way to interpret and present data in descriptive form. The existing data is then interpreted and analyzed. The plant has a close relationship with the Ngaju Dayak community as food and boards, plants that are one of the requirements in the Ngaju Dayak traditional ritual, and the plant is used as a symbol or metaphor. The animal phenomenon that appears in Ngaju Dayak folklore is caused by the animal is around the settlement and becomes a myth for the Ngaju Dayak people, it is useful as a source of nutrition it is used in traditional ceremonies, traditional rituals and is related to traditional ceremonies it has a specific meaning and. The phenomenology of plants that appear in the folklore studied is the use of words or phrases wood 'tree', banana 'banana', kambang 'flower', uwei 'rattan', sangkai puca, sambilu /bamboo', upun pinang 'batang pinang'. The phenomenology of animals that appear in the folklore studied is the use of words or phrases handipe, cow, manuk, burong, side dishes, bawui, haramaung, elephants with palanduk, and calasi.